2008
DOI: 10.1080/03079450701784875
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and repeated lipopolysaccharide administration on body temperature and the concentration of interleukin-6 and IgM antibodies against lipopolysaccharide in broiler chickens

Abstract: Our objective was to create a standardized and reproducible inflammation model in chickens in order to study the pharmacodynamics of several anti-pyretic and anti-inflammatory drugs. We studied the influence of age and repeated lipopolysaccharide (LPS) administration on body temperature and the correlation of this with concentrations of interleukin-6 and IgM antibodies against LPS in plasma of chickens. Three-week-old and 5-week-old broilers were injected intravenously with LPS from Escherichia coli O127: B8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 46 publications
(50 reference statements)
5
30
0
3
Order By: Relevance
“…Our first scenario is supported by evidence that 1) innate immune activation triggers the release of IL-6 in birds (9,27), 2) avian thrombocytes, a major component of the innate immune system in birds, upregulate their expression of IL-6 mRNA, as well as the important PG-synthesizing enzyme COX-2, after immune challenge (41), and 3) chickens develop fever following hypothalamic injection of PGE 2 (1). There is convincing evidence that IL-6 and PGE 2 are critically important for febrile mediation in mammals (5,29,35), even though the mechanism by which IL-6 instigates changes in the central nervous system to cause fever in mammals is still controversial.…”
Section: Effect Of Systemic Diclofenac On Centrally Induced Il-1␤ Feversupporting
confidence: 57%
See 3 more Smart Citations
“…Our first scenario is supported by evidence that 1) innate immune activation triggers the release of IL-6 in birds (9,27), 2) avian thrombocytes, a major component of the innate immune system in birds, upregulate their expression of IL-6 mRNA, as well as the important PG-synthesizing enzyme COX-2, after immune challenge (41), and 3) chickens develop fever following hypothalamic injection of PGE 2 (1). There is convincing evidence that IL-6 and PGE 2 are critically important for febrile mediation in mammals (5,29,35), even though the mechanism by which IL-6 instigates changes in the central nervous system to cause fever in mammals is still controversial.…”
Section: Effect Of Systemic Diclofenac On Centrally Induced Il-1␤ Feversupporting
confidence: 57%
“…For this reason, we chose to measure PGE 2 concentrations in the CSF of Pekin ducks 150 min after LPS treatment, during the rising phase, but before the peak of fever. Previous studies with birds confirmed that systemic LPS treatment initiates an increase in plasma IL-6 concentrations (9,27), and there is evidence that, in pigeons, LPS stimulates peripheral PG synthesis (32).…”
Section: Absence Of Pge 2 In Csf Of Lps-treated Pekin Ducksmentioning
confidence: 95%
See 2 more Smart Citations
“…2, 194-203, http://dx.doi.org/10.1080/09540105.2014 bacteria and could stimulate animals to produce innate immune response to change the nutrient metabolism, which would significantly reduce the growth rate of animals. Benson, Calvert, Roura, andKlasing (1993), Fraifeld, Blaicher-Kulick, Degen, andKaplanski (1995), Baert, Duchateau, De Boever, Cherlet, andDe Backer (2005) andDe Boever et al (2008) all observed the increased body temperature after repeated injections of LPS, but did not explain this change from a nutritional point of view.…”
Section: Introductionmentioning
confidence: 90%